Efficient Consumer Response in Fast Food Supply Chain Management of Hamburgers for Compliance, Health and Marketability - John Jeyasingam Thambirajah (International Journal of Supply Chain Management, 2021)
Foods of animal origin are a good source of high quality protein. However, determining fat content in hamburgers is important in order to minimize the adverse effects on health. Cardiovascular disease and obesity are known to be caused by high consumption of saturated fatty acids and cholesterol. Efficient consumer response in fast food Supply chain management is a strategy designed to make fast food industry more efficient, safe and responsive to the consumer’s needs. This study conducted confidence interval estimation to assess variation in the fat content of hamburger samples from a restaurant, using Minitab. The standard for mean fat content was set at 15 grams with a standard deviation of 1 gram. In this study twenty samples were selected at random and statistical process control was determined by the individual moving range (I-MR) test. The I-MR chart conducted on twenty individual hamburger samples showed that the fat content was in statistical process control. A graphical summary was conducted to check for normality by the Anderson-Darling test and 95% confidence interval of the mean and standard deviation were determined. The p-value for Anderson-Darling was not significant indicating that the samples were normally distributed. The mean read at 16.48 grams with a standard deviation of 2.09. The confidence interval for the mean registered between 15.50 to 17.46 grams. A variance test was carried out to determine a less than 1 gram variation in the samples. The upper bound was detected in a Chi square test at 8.24. A confidence interval estimation for population proportion showed 0.16 for the upper bound. An automatic oil dispensing machine was installed to standardize the oil applied for frying each hamburger. Another 20 samples were taken and were found to be in statistical process control by the I-MR test. A graph summary report indicated a mean of 14.92 grams and standard deviation of 0.49 grams. The Anderson-Darling test was not significant at p-value of 0.924.Thus confirming a normal distribution. The 95% confidence interval now registered at 14.69 to 15.15, which was close to the expected value of 15 grams. A survey conducted on 100 and 350 customers selected at random, before and after the installation of the automatic oil dispensing machine showed that there were now less dissatisfied customers. A simulation test carried out with twenty samples of 10 subgroups each showed that the process was in control in an X-bar S-chart. An interval plot conducted using a simple multiple Ys chart showed that all the samples were within the 95% confidence interval for the mean indicated by the reference line. A process capability analysis conducted before and after the installation of the automatic oil dispensing machine indicated that the process could be improved further. Key words: Fat content, hamburgers, confidence interval, variation, statistical process control